The Effectiveness of Student-Initiated Media in Developing the Speaking Performance of Junior-High-School Students - Maslikah, Khotim; Widiati, Utami (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
This article reports the effectiveness of student-initiated media in teaching speaking to ninth graders of a junior high school. Using a pre-experimental design, this study involved 85 students, being given an experimental treatment in the form of a freedom to choose and use their own media to present an English advertisement, one of the basic competences the students had to master in the semester when the data were being collected. A pre-test in the form of oral interview was given at the beginning of the study, followed by the implementation of the research treatment. At the end of the study, the students took a post-test of a similar format. In other words, the data in this study were in the form of the students’ speaking performance. With the help of SPSS, a test was employed to check the effectiveness of the media. Besides, informal interview with the students show that they felt more relaxed and less anxious when using the media while speaking. It is recommended that teachers make use of such media in the classroom for designing democratic classroom atmosphere so that students experience joyful learning and tend to speak more.